Penganggar MM bagi model linear dengan titik musnah dan kecekapan yang tinggi - Midi, Habshah (Penerbit Universiti Kebangsaan Malaysia, 1997)
A robust MM estimates for the linear model is revisited. This estimates are defined by a three-stage procedures and posses the following properties: (i) they are highly efficient when the errors have a normal distribution and (ii) their breakdown-point is 0.5. A numerical examples are used to show that the MM estimates has a higher breakdown point and is more efficient than The RLS (Reweighted Least Squares Regression based on The Least Median Squares) estimates.